Formation of Ecological Culture of Students in the Conditions of Distance Learning - Liza Grineva; Marina Alekseeva; Larisa Kazakova; Marina Zabbarova (ARPHA Proceedings, 2022)
The environmental situation that has developed in Russia and around the world, the global nature of environmental problems and their peculiar manifestation in each region of the planet urgently require an early change of the thinking of humanity, individual peoples and each individual person. One of the reasons for this situation is the environmental illiteracy of the majority of the population and the inability to foresee the consequences of human intervention in nature. In this regard, environmental education as a continuous process is becoming a new priority area of pedagogical theory and practice. The importance of environmental education in modern world is beyond doubt. It is also obvious the earlier a child learns the basics of ecology, the more environmentally literate he will be, no matter what profession he will choose. Of particular interest today is the study of the impact of distance learning on the formation of environmental culture, especially during the coronavirus pandemic, which has provoked implementation of e-learning and distance learning technologies everywhere. Based on the above, the purpose of the study is to identify the impact of distance learning on the formation of environmental culture of schoolchildren. The following methods were used in the study: analysis of scientific and methodological and psychological-pedagogical literature; questionnaire (questionnaire "Studying the influence of distance learning on the formation of environmental culture of schoolchildren"); testing; mathematical processing of the data obtained.